2018
DOI: 10.1128/iai.00597-17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Cytokine Genes in Colombian Patients with Ocular Toxoplasmosis

Abstract: Toxoplasmosis is caused by infection with the protozoan parasite , which has the capacity to infect all warm-blooded animals worldwide. Toxoplasmosis is a major cause of visual defects in the Colombian population; however, the association between genetic polymorphisms in cytokine genes and susceptibility to ocular toxoplasmosis has not been studied in this population. This work evaluates the associations between polymorphisms in genes coding for the cytokines tumor necrosis factor alpha (TNF-α) (rs1799964, rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 82 publications
(90 reference statements)
4
24
0
Order By: Relevance
“…Regarding the IFN-γ promoter (SNP rs2430561) polymorphism, we found that individuals with the T/T genotype produced higher levels of IFN-γ than those with T/A alleles. This results are in agreement with the findings from previous studies (De Albuquerque et al, 2009; Neves et al, 2013; Naranjo-Galvis et al, 2018) where the A-allele was found to enhance susceptibility to OT, and also shown the importance of host genetics in terms of IFN-γ secretion in the anti-parasite response. The T/T genotype has previously been reported to be associated with protection against the retinochoroiditis caused by toxoplasmosis (De Albuquerque et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the IFN-γ promoter (SNP rs2430561) polymorphism, we found that individuals with the T/T genotype produced higher levels of IFN-γ than those with T/A alleles. This results are in agreement with the findings from previous studies (De Albuquerque et al, 2009; Neves et al, 2013; Naranjo-Galvis et al, 2018) where the A-allele was found to enhance susceptibility to OT, and also shown the importance of host genetics in terms of IFN-γ secretion in the anti-parasite response. The T/T genotype has previously been reported to be associated with protection against the retinochoroiditis caused by toxoplasmosis (De Albuquerque et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The next question we addressed was whether polymorphisms in the host's immune system-related genes were associated with differences in cytokine secretion from the PBMCs infected with T. gondii . We investigated this because during toxoplasmosis infection, polymorphisms in both IFN-γ (rs2430561) and IL-10 (rs1800871) and the “GAG” haplotype in the IL-1β gene's promoter (SNPs at rs1143634, rs1143627, rs16944) are associated with the development of OT in the Colombian population (Naranjo-Galvis et al, 2018). Regarding the IFN-γ promoter (SNP rs2430561) polymorphism, we found that individuals with the T/T genotype produced higher levels of IFN-γ than those with T/A alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are only very few animal studies using these atypical strains [ 98 ], the pathophysiology of these infections is still largely unknown. Interestingly, human genetic disposition, mainly concerning immune response genes, also seems to be an important factor to determine the development of severe disease [ 99 ]. The high frequency of pathological cases in South America surely will result in more interesting human studies regarding genetic predisposition.…”
Section: Enhanced Virulence: Toxoplasma Infection mentioning
confidence: 99%
“…Previous studies had demonstrated that these three polymorphisms were proposed to affect the transcription efficiency and expression of the IL-10 gene [41]. More than 70% of the individual variability in human IL-10 production has been attributed to genetic variation, which could help to predict patient susceptibility to the disease as well as the severity and progression of the disease [42][43][44]. For the -1082A>G polymorphism, the A allele demonstrated a higher binding affinity to the transcription factor PU.1, resulting in decreased transcriptional activity and lower expression level of IL-10 [45].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%